Isolation, identification and activities of natural antioxidants from Callicarpa kwangtungensis Chun. - Hao Cai (Public Library of Science (PLoS), 2014)
Reactive oxygen species leads to some diseases associated with oxidative stress. Callicarpa kwangtungensis Chun (CK) is a common remedy in traditional Chinese medicine and possesses diverse biological activities involving antioxidant properties; its main compounds phenylethanoid glycosides (PG) and flavonoids are always reported as antioxidants. In order to develop CK as a safe and activated antioxidant, our investigation was performed to validate antioxidant properties and assess which types of compounds (similar polarity or similar structure), even which compounds, played the role of antioxidants. The extracted compounds of CK were analyzed qualitatively and quantitatively by HPLC-DAD-ESI-Trap MS and UV for their contents and antioxidant activities. The correlations between antioxidant activities and known contents were respectively counted and a semi-quantitative experiment was designed to screen antioxidant compounds of CK with HPLC-UV. The n-butanol fraction (BF) showed the highest total phenolic and flavonoid contents (TPC, TFC), and three PG (forsythiaside B, poliumoside and acteoside) contents. BF showed the significantly best (P<0.05) activities in most assays. There were significant correlations (P<0.05) between DPPH•, ABTS(+)•, •O2(-) scavenging, Cu(2+)-chelating, anti-lipidperoxidation activities and TPC. BF also has significant antioxidant activities on CCl4-induced acute liver injury Mice and TBHP-reduced HepG2 cells. Nine PG (forsythiaside B, poliumoside, acteoside, alyssonoside, brandioside and their derivatives) and one flavone (rhamnazin) were screened out as antioxidants. BF in CK contained abundant polyphenolic, which reflected some definite antioxidant properties. The antioxidant compounds consisted at the least of nine PG and one flavone.